Mesenchymal stem/stromal cells in the pathogenesis and regenerative therapy of inflammatory bowel diseases - Che, Zhengping; Ye, Ziyu; Zhang, Xueying; Lin, Bihua; Yang, Weiqing; Liang, Yanfang; Zeng, Jincheng (Frontiers in Immunology, 2022)
Inflammatory bowel diseases (IBDs) represent a group of chronic inflammatory disorders of the gastrointestinal (GI) tract including ulcerative colitis (UC), Crohn’s disease (CD), and unclassified IBDs. The pathogenesis of IBDs is related to genetic susceptibility, environmental factors, and dysbiosis that can lead to the dysfunction of immune responses and dysregulated homeostasis of local mucosal tissues characterized by severe inflammatory responses and tissue damage in GI tract. To date, extensive studies have indicated that IBDs cannot be completely cured and easy to relapse, thus prompting researchers to find novel and more effective therapeutics for this disease. Due to their potent multipotent differentiation and immunomodulatory capabilities, mesenchymal stem/stromal cells (MSCs) not only play an important role in regulating immune and tissue homeostasis but also display potent therapeutic effects on various inflammatory diseases, including IBDs, in both preclinical and clinical studies. In this review, we present a comprehensive overview on the pathological mechanisms, the currently available therapeutics, particularly, the potential application of MSCs-based regenerative therapy for IBDs.